Help-seeking for depression among Vietnamese migrant workers in Japan and factors related to their intentions to seek help from a psychiatrist: a cross-sectional study - Yui Fukuda; Atsuko Taguchi; Akane Futami; Yusuke Umegaki; Pham Nguyen Quy; Toshihiko Nakajima; Akihito Uezato (BMC Public Health)
Abstract Background Foreign workers are at risk for depression, and Vietnamese people tend to be reluctant to seek professional mental health care. Although Vietnamese people are the largest population among foreign workers in Japan, evidence concerning their help-seeking experiences and strategies to promote help-seeking in this population is lacking. This study aimed to identify the percentage of Vietnamese migrant workers in Japan who have sought help from healthcare professionals for depressive symptoms and to explore the factors related to their intentions to seek help from a psychiatrist. Methods An online questionnaire was administered to Vietnamese migrants working in Japan from October 5, 2021, to November 1, 2021. Patient Health Questionnaire-9 (PHQ-9) scores were calculated to measure the severity of the respondents’ depression. Help-seeking experiences related to depressive symptoms were also investigated. The General Help-Seeking Questionnaire Vignette Version (GHSQ-V) was modified and adapted to measure the respondents’ intention to seek help from a psychiatrist for depressive symptoms. To investigate the factors related to help-seeking intention, potential factors were selected from literature reviews and discussions with professionals in the field. Descriptive statistics were calculated, and multiple logistic regression analysis was conducted. Results A total of 803 eligible data points were collected. Among the 53.5% of participants who scored 10 or more on the PHQ-9, 4.4% had sought help from a healthcare professional in Japan. A lower preference for coping on one’s own, greater recognition of the effectiveness of help, greater ability to make work adjustments, and a higher level of Japanese language proficiency were related to greater intentions to seek help from a psychiatrist. Conclusions Many Vietnamese migrant workers in Japan are unable to seek help from healthcare professionals for depressive symptoms. It may be beneficial to acknowledge not only linguistic barriers but also other related factors when planning strategies to enhance Vietnamese migrant workers’ intentions to seek help from psychiatrists.